Backward-Compatibility Effects With Irrelevant Stimulus-Response Overlap: The Case of the SNARC Effect. - Caessens, Bernie; Hommel, Bernhard; Reynvoet, Bert (Journal of General Psychology, 2004)
In 3 dual-task experiments, the relationship between primary-task response (R1) and secondary-task response (R2) was varied. In general, RI-left responses were faster when followed by the word one, and right responses were faster when followed by the word two. This backward-compatibility (BWC) effect indicated (a) that activation of R2 was not delayed until R1 selection was completed, and (b) that activation of the vocal responses was accompanied by the automatic activation of magnitude codes, known to be associated with spatial left-right codes (spatial-numerical association of response codes {the SNARC effect}). These findings supported the hypotheses (a) that BWC effects persist even with irrelevant R1-R2 overlap, (b) that the SNARC effect is based on associations between magnitude and spatial representations underlying response processing, and (c) that the production and perception of magnitudes relies on common codes. Reprinted by permission of the publisher.